Farmers' cognition of the COVID-19 outbreak, risk perception and willingness of green production. (20th December 2022) - Luo, Lei; Qiao, Dakuan; Wang, Lishuang; Qiu, Ling; Liu, Yuying; Fu, Xinhong
Abstract: Existing literature reports that COVID-19 outbreak may affect people's risk perceptions, with disturbances ranging from mild negative emotional reactions to overall mental health. At the same time, the pneumonia pandemic reveals all the vulnerabilities and weaknesses of our ecosystem and makes people reflect on traditional ecologically harmful production practices. Therefore, the aim of this paper is to review the existing scientific literature on these variables, through a survey and empirical analysis, in order to present and comment on the effects and mechanisms of influence between them. The results showed that: (1) Increasing farmers'cognition of COVID-19 outbreak could significantly enhance the green production willingness. Specifically, the probability of "Very willing"to participate in green production increased by 29.9% for each unit of increase in cognition. (2) Farmers'cognition of COVID-19 outbreak can significantly enhance the level of risk perception and thus enhance their green production willingness, that is, risk perception is an important transmission medium of this effect. (3)The analysis of inter-generational difference showed that the impact of cognition of COVID-19 outbreak on green production willingness was significant for both the new generation and the old generation. On the basis of this, some policy suggestions are put forward, such as strengthening the propaganda and education of natural ecological environment protection, establishing the propaganda mechanism of green agricultural products market in the later period of epidemic situation, raising farmers'risk perception level through multi-channels and so on.